ESL students' self-perceived, actual performance and learning needs in oral presentations: a case study / Nor Fathiah Alwi - Alwi, Nor Fathiah (2015)
The main aim of this study was to investigate ESL students’ learning needs in oral presentations. Therefore, the study looked into the students’ self-perceived and actual performance in oral presentations and the amount of help they needed in oral presentation skills with regard to organisation, content, delivery and language. Besides that, this study also investigated students’ attitude, motivation and learning orientation towards oral presentations. The case study was conducted in a public university located in Selangor, Malaysia. It involved a randomly selected intact group of 40 ESL students and two lecturers teaching the Oral Communication Course. The data were collected using a needs analysis questionnaire, an oral presentation test and semi-structured interviews. The quantitative data were analysed using the SPPS Version 20.0 and involved the use of both descriptive and inferential statistics whilst qualitative data was deductively and inductively analysed to answer the research questions in the study. The findings revealed that students had a very positive attitude towards oral presentations and they were motivated to learn oral presentation skills. Besides that, findings also revealed that these students prefer teacher-directed lessons with opportunities for them to practice group oral presentations where immediate oral feedback could be obtained from the lecturer. More importantly, the results showed that there was a significant difference in students’ self-perceived and actual performance with regard to delivery and language but no significant differences were seen in terms of organisation and content. In terms of delivery the students highlighted the need to improve their articulation, enunciation and how to avoid verbal pauses so that they could speak in a professional manner. With regard to language, the students’ learning needs included the ability to speak accurately using a wide range of vocabulary and sentence patterns. Learning needs in terms of organisation focussed on students’ ability to synthesise information and the use of connectives and discourse markers to present a coherent speech whilst learning needs for content focussed on students’ need to prepare well-researched speeches with relevant supporting details and summing up with an appropriate conclusion. Based on these findings, this study has proposed an instructional framework which encompasses not only the elements of oral presentations but also aspects such as learning orientation, attitude and motivation. The findings in this study also imply that it is important that the lecturers teaching tertiary students focus on teaching students oral presentation skills using a carefully designed oral presentation course tailored to address the specific students’ learning needs.